Implementation of the Kurikulum Merdeka in high school physical education - Sigit Hari Prasetyo; Zihan Novita Sari (Himpunan Pengembang Kurikulum Indonesia, 2025)
Kurikulum Merdeka introduces a transformative approach to Indonesian education, focusing on character development and student competencies. This study aims to evaluate the level of implementation, challenges faced by teachers, and factors influencing the success of the Kurikulum Merdeka in Physical Education, Sports, and Health subjects at the high school level in Bontang City, addressing gaps in understanding its application. Using a mixed-methods design, the research employed surveys and interviews with 16 Physical Education, Sports, and Health teachers. The questionnaire was tested for validity and reliability with 37 respondents outside the study sample, indicating high reliability. The results reveal that implementing the Kurikulum Merdeka in Physical Education, Sports, and Health subjects falls under the